Causes and consequences of the shortage of physicians in Sindh, Pakistan: a local perspective - Khan, Rehan (Journal of the Pakistan Medical Association, 2023)
The narrative review was designed to investigate potential factors that contribute to the shortage of primary care and specialty care physician workforce in Sindh, Pakistan, and how the disparity contributes to the proliferation of medical quackery across the province. There are serious consequences for the patients, putting additional strain on Sindh's healthcare system. Pakistan is one of the many countries where the demand for doctors is outpacing the supply. The province of Sindh lacks the medical personnel necessary to address its healthcare needs. Since there is a greater need than supply of general practitioners and specialists, there may be a growing gap between the healthcare workforce and patient care which may reinforce mounting physician shortage in the future due to factors, such as an ageing physician population, an escalating general population, and the fact that many doctors are nearing retirement age. Key Words: Physicians shortage, Causes, Implications, Quackery, Sindh.